Electrochemotherapy for the palliative management of non-skin-origin head and neck cancer: case series and UK national survey. Issue 3 (25th March 2022) - McCaffer, C; Wong, B Y W; Murugan, C S; Muir, T; Lester, S
Abstract: Objectives: Electrochemotherapy uses electric fields to facilitate the influx of chemotherapy into cancer cells, producing a targeted effect. For head and neck cancer, it is mainly used for palliation of non-skin-origin metastases. It is used infrequently in the UK. This paper presents our experience and a UK survey to identify its frequency of use. Methods: Between 2016 and 2019, a prospective database was created and reviewed. Only patients with non-skin-origin metastatic head and neck cancer, with no other palliative options, were included. Survival length, complications and symptomatic benefit were assessed. The survey was conducted via e-mail. Results: Five patients were included: three with squamous cell carcinoma, one with esthesioneuroblastoma and one with hepatocellular carcinoma. Survival ranged from 1 month to over 20 months. Minor complications were seen. Only 15 out of 69 UK head and neck multidisciplinary teams offer electrochemotherapy. Conclusion: Electrochemotherapy is a well-tolerated adjunct to standard palliation of metastatic head and neck cancer, and is offered by a limited number of UK multidisciplinary teams.